Precision Farming in Paddy as an option to increase Resource Use Efficiency - K. Shruthi; G. M. Hiremath; Suresh S. Patil; Amrutha T. Joshi; M. B. Patil (Journal of Agricultural Extension Management, 2015)
Precision Farming helps in dealing with the challenge of accurate agricultural management practices with improved technology which have the potential to benefit the farmer financially through proper and effective management of soil and crop variability with the use of information technology. Precision Farming differs from conventional farming that is based on uniform treatment across a field. It involves application of technologies like mapping and analyzing field variability and linking spatial relationships to management action, thereby allowing farmers to look at their farms, crops and practices from an entirely new perspective. Considering its benefits, in the present paper an attempt has been made to analyze the productivity of various resources in production of paddy under precision farming over non-precision farming in the study area where precision farming has been implemented. Cobb-Douglas type of production function was fitted to the farm level data to study the efficiency of various inputs in precision and non-precision farming of paddy. The allocative efficiency in the use of each resource was calculated by constructing the ratio of Marginal Value Product (MVP) to the Marginal Factor Cost (MFC). Results indicated that there was excess utilization of N and K2O fertilizers under non-precision farming. Increasing returns to scale was noticed in precision farming whereas diminishing returns to scale was noticed in non-precision farming. There is a need to popularize the precision farming method of cultivation of paddy among the farming community considering its benefits like savings in resources and thereby reduction in cost of cultivation.